(untitled) (Texas Journal of Medical Science, 2022)
Coronavirus disease (COVID – 19) was one of the most severe pandemics that the world has ever seen. The infection ranges from asymptomatic, mild to life threatening respiratory distress. It can affect almost every organ of the body, including the organ of vision. Ophthalmic manifestations may be present in the course of COVID-19 infection or they may develop later in rehabilitation period. The aim of the research is to facilitate the diagnostics and initiation of comprehensive therapy of pathological eye conditions of ocular surface and cornea that occur in coronavirus disease